Development of digital skills in higher education - Arias Oliva, Mario; Torres Coronas, Teresa; Yález Luna, Juan Carlos (Historia y Comunicación Social, 2014)
Our research focus on skills acquired by degree students in Universitat Rovira i Virgili. We analyze competences in ICT area to determine if students are “digital natives”. Our literature review concluded ICT use is a critical competence nowadays. We conclude that universities should take part in the development of these skills by developing a holistic learning environment based on technological tools.
Keywords: Digital skills; Web 3.0; e-Learning